The histone variant H3.3 G34W substitution in giant cell tumor of the bone link chromatin and RNA processing - Lim, Jinyeong; Baude, Annika; Fellenberg, Jörg; Plass, Christoph (Scientific reports, 2017)
While transcription as regulated by histones and their post-translational modifications has been well described, the function of histone variants in this process remains poorly characterized. Potentially important insight into this process pertain to the frequently occurring mutations of H3.3, leading to G34 substitutions in childhood glioblastoma and giant cell tumor of the bone (GCTB). In this study, we have established primary cell lines from GCTB patients and used them to uncover the influence of H3.3 G34W substitutions on cellular growth behavior, gene expression, and chromatin compaction. Primary cell lines with H3.3 G34W showed increased colony formation, infiltration and proliferation, known hallmarks of tumor development. Isogenic cell lines with H3.3 G34W recapitulated the increased proliferation observed in primary cells. Transcriptomic analysis of primary cells and tumor biopsies revealed slightly more downregulated gene expression, perhaps by increased chromatin compaction. We identified components related to splicing, most prominently hnRNPs, by immunoprecipitation and mass spectrometry that specifically interact with H3.3 G34W in the isogenic cell lines. RNA-sequencing analysis and hybridization-based validations further enforced splicing aberrations. Our data uncover a role for H3.3 in RNA processing and chromatin modulation that is blocked by the G34W substitution, potentially driving the tumorigenic process in GCTB.